2018
DOI: 10.7575/aiac.ijalel.v.7n.3p.125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Individualized Technology-Mediated Feedback on EFL Learners’ Argumentative Essays

Abstract: This quantitative quasi-experimental study, which followed a pretest-posttest-delayed posttest design, was aimed at investigating the effect of individualized technology-mediated feedback (henceforth, ITMF) on the overall quality of Iranian EFL learners’ argumentative essays. The effect of ITMF, as the experimental treatment, was compared with the common written corrective feedback (henceforth, CWCF) strategies as the control treatment. 57 learners, studying at general EFL courses at upper-intermediate level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
(200 reference statements)
0
3
0
Order By: Relevance
“…Another ICT tool that can be used is video, which can also be used for providing feedback. The students are required to watch videos and revise their work (Soltanpour & Valizadeh, 2018). Feedback from peers and instructors can also be given by using audio tracks or any audiovisual media (Kawinkoonlasate, 2021).…”
Section: Ict Tools For Providing Feedbackmentioning
confidence: 99%
“…Another ICT tool that can be used is video, which can also be used for providing feedback. The students are required to watch videos and revise their work (Soltanpour & Valizadeh, 2018). Feedback from peers and instructors can also be given by using audio tracks or any audiovisual media (Kawinkoonlasate, 2021).…”
Section: Ict Tools For Providing Feedbackmentioning
confidence: 99%
“…Quantitative studies (n = 28) demonstrated a positive impact or perceived positive impact of the use of digital technology-supported writing instruction on participants' overall writing skills. First, 11 studies indicated significant performance differences between students who used the technology for writing instruction and students in the control group (Adas & Bakir, 2013;Hung & Young, 2014;Khoshsima & Sayadi, 2016;Lin et al, 2018;Marleni, 2020;Soltanpour & Valizadeh, 2018a;Soltanpour & Valizadeh, 2018b;Sujannah et al, 2020;Yang et al, 2019;Yu & Wang, 2016;Zaini & Mazdayasna, 2015). Second, 10 studies found that instruction incorporating DVDs/videos to support writing instruction helped participants improve their writing skills (Adas & Bakir, 2013;Chen & Su, 2012;Damavandi et al, 2018;Hsu, 2013;Kumar & Sultana, 2016;Lin et al, 2018;Noyan & Kocoglu, 2019;Soltanpour & Valizadeh, 2018a;Soltanpour & Valizadeh, 2018b;Yu & Wang, 2016).…”
Section: Tablementioning
confidence: 99%
“…Using videos for teaching English as Foreign Language (EFL) is considered to be helpful in developing language skills (Ali, 2016;Chae, 2018;Crews & Wilkinson, 2010;Henderson & Phillips, 2015;Maru et al, 2020;Soltanpour & Valizadeh, 2018). The use of videos increases learners' interest and motivation to learn (Xhemaili, 2013) and stimulates skill acquisition; it is also effective for language practices (Maru et al, 2020).…”
Section: Introductionmentioning
confidence: 99%